Dammarane Sapogenins Improving Simulated Weightlessness-Induced Depressive-Like Behaviors and Cognitive Dysfunction in Rats - Wang, Qiong; Dong, Li; Wang, Mengdi; Chen, Shanguang; Li, Shanshan; Chen, Yongbing; He, Wenlu; Zhang, Hong; Zhang, Yongliang; Pires Dias, Alberto Carlos; Yang, Sijin; Liu, Xinmin (Frontiers in Psychiatry, 2021)
Background Studies have found that the space environment has an impact on the brain function of astronauts. Numerous ground-based microgravity and social isolation studies have also shown that the space environment can cause brain function damage in humans and model animals. Dammarane sapogenins (DS), an active fraction from oriental ginseng, has been reported to have neuroprotective effects and to improve memory. This study aimed to explore the effects and mechanisms of DS in attenuating depressive-like behaviors and cognitive deficiency induced by simulated weightlessness and isolation (HLSI) in rats. Methods Male rats were treated with two different doses of DS (37.5, 75 mg/kg) for 14 days by oral administration, and Huperzine-A (1 mg/kg) group was the positive control group. Rats were submitted for 14 days to HLSI except the control group. The depressive-like behaviors were evaluated by the open filed test, novel object test, and forced swimming test. The spacial memory and working memory enhancing effects of DS were evaluated by the Morris water maze (MWM) test and the related mechanism was further explored by analyzing the activity of choline acetyltransferase (ChAT), acetylcholinesterase (AChE) and superoxide dismutase (SOD) in the hippocampus of rats. Results The results showed that DS treatment significantly reversed the HLSI induced depressive-like behaviors in the open field test, the novel object test, the forced swimming test, and improved the HLSI induced cognitive impairment in the MWM test. Furthermore, the ChAT and SOD activities of HLSI rats were obviously increased after DS treated, and DS significantly suppressed the activity of AChE in the HLSI rats. Conclusions These findings demonstrated that DS might exert a significant neuroprotective effect on cognitive dysfunctions induced by spaceflight environment, driven in part by the modulation of cholinergic system in the hippocampus.